2017
DOI: 10.3390/pr5030040
|View full text |Cite
|
Sign up to set email alerts
|

Development of Molecular Distillation Based Simulation and Optimization of Refined Palm Oil Process Based on Response Surface Methodology

Abstract: Abstract:The deodorization of the refined palm oil process is simulated here using ASPEN HYSYS. In the absence of a library molecular distillation (MD) process in ASPEN HYSYS, first, a single flash vessel is considered to represent a falling film MD process which is simulated for a binary system taken from the literature and the model predictions are compared with the published work based on ASPEN PLUS and DISMOL. Second, the developed MD process is extended to simulate the deodorization process. Parameter est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 13 publications
(9 reference statements)
0
14
0
Order By: Relevance
“…Some of the recent works on modelling carried out using commercial simulation software are worth mentioning. In a recent work, Tehlah et al 18 developed a simulation model based on Aspen HYSYS for a molecular distillation column that is used for deodorisation of refined palm oil; the model was later optimised with the aid of response surface methodology (RSM). Another work by Kamarden et al 19 reported a simulation model based on Aspen Plus for integrated palm oil processes involving milling refining and oleochemical production.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the recent works on modelling carried out using commercial simulation software are worth mentioning. In a recent work, Tehlah et al 18 developed a simulation model based on Aspen HYSYS for a molecular distillation column that is used for deodorisation of refined palm oil; the model was later optimised with the aid of response surface methodology (RSM). Another work by Kamarden et al 19 reported a simulation model based on Aspen Plus for integrated palm oil processes involving milling refining and oleochemical production.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental result showed that all surfactants had a significant impact at high temperature and dosage of surfactant. Thus, RSM was utilised for designing the experimental, analysing the parameters dependent on analysis of variance, and developing the quadratic polynomial formal based model to study the influence of parameters on response and optimisation of the condition of process [23,24]. Moreover, the non-ionic surfactant is less used in demulsification of water in oil emulsion in comparison with other types of surfactant [2], while the properties of non-ionic surfactant are very promising.…”
Section: Introductionmentioning
confidence: 99%
“…Oil sample was considered as a mixture of mono-, di-and triglycerides; tocopherols; and fatty acids identified as majority in composition of Camelina sativa oil. All compounds are in the simulator database and their properties were calculated using RK-ASPEN (Redlich-Kwong Soave with Wong-Sandler mixture rules) properties package [27]. The molecular distillation unit was modeled by combination of three simulator models: HeatX-Flash2-HeatX, for light molecule evaporation, vaporized molecule migration, and condensation, with mixture temperature and pressure as specifications.…”
Section: Process Design Economic and Environmental Analysismentioning
confidence: 99%